Analisis Persiapan Guru Dalam Pelaksanaan Pembelajaran Matematika Di Kelas V SD Negeri 14 Tilamuta - Paulu, Irmawati; Supu, Lisfan; Haka, Nur Ain; Nuwa, Nur Laila; Ilato, Susanti; Uno, Winda Anggriyani (PT MEDIA JURNAL DAN PENDIDIKAN, 2023)
This research aims to find out what preparations are made by class V teachers in implementing mathematics learning. The method used in this research is qualitative research with descriptive analysis. The subjects this research were class V students who provided research data through interviews. The informant in this research was the fifth grade teacher ad SD Negeri 14 Tialmuta. The data analysis used in this research is adat reduction, data presentation, and verification. In this research,researchers produced findings about the preparations carried out by teacher in implementing mathematics learning, including preparing a learning implementation plan (RPP). Learning media, learning methods and learning evaluation. The obstacle in learning preparation is that many students cannot calculate and memorize multiplication and many students are not serious about studying mathematics.